Epidemiology, evolution, and biological characteristics of H3 avian influenza viruses isolated from chickens in China - Minghui Li; Xiaojing Gao; Yunjing Zhang; Dongying Du; Wanbing Wang; Sumei Hong; Jialei Duan; Hui Tian; Lulu Wang; Zhuoyi Li; Wenqiang Pang; Kegong Tian (One Health)
During an epidemiological investigation of avian influenza viruses (AIVs) in China, we isolated four H3 AIVs from chickens. To investigate the genetic relationships of these Chinese isolates with the globally circulating H3 viruses, we performed a detailed phylogenic analysis of the hemagglutination (HA) genes of 2613 representative H3 viruses available in the public source, and found that the HA genes of H3 viruses in China evolved from the Eurasian lineage and became established in domestic Anseriformes (primarily ducks). Bayesian phylodynamic analysis revealed that the Southern China (Guangdong and Guangxi provinces) served as a hub for the H3 virus diffusion to other parts of China, and the virus dissemination was potentially primarily driven by domestic ducks. Of note, the rate of H3N8/H3N3 virus detection had been increasing since 2021, and the main host of these H3 viruses appeared to have shifted from ducks to chickens, posing a potential pandemic threat within poultry populations. Here we showed that changes in amino acid substitutions located at antigenic sites around the receptor binding pocket of the HA protein, together with internal gene recombination of G57 H9N2 viruses, causing altered antigenicity and improved adaptability in chickens. The four H3 isolates in this study acquired multiple mutations for mammalian adaption, and presented increased pathogenicity in mice. These findings emphasize that the continued evolution of these H3 viruses in poultry poses ongoing economic and pandemic threat, and highlight the need for continued surveillance of H3 viruses from poultry.